Facing the Industrial Revolution 4.0: Increasing Teacher Competence through the Technical Guidance on Making Digital Teaching Materials - Fanny Rahmatina Rahim (Fakultas MIPA Universitas Negeri Padang, 2021)
Indonesia faces the biggest challenge in education. The problem is teachers have not used IT in learning. Teachers in partner schools still maintain conventional learning so interactive training in teaching material is needed. The training was about using the Kvisoft Flipbook Maker (KFM) application to prepare students to compete in science and technology. By using the KFM program, teaching materials become more interesting because they are equipped with animations and videos that can increase student interest in learning. This paper explains about training activities and produces digital teaching materials. Partners in this activity were the teachers at SMAN 2 Palembayan. The implementation method used consists of four activities, namely: preparation, implementation, monitoring and evaluation, as well as analysis and reporting.